Some adjunctions associated with extensions and restrictions of ideals in the context of commutative rings (2013)
Given a commutative ring R and S one of its ideals, the function I -- and gt; (I : S) that transforms ideals of R into ideals of R, is right adjoint of the function I -- and gt; IS. We define the S−maximal ideals of R as those ideals J of R such that (J : S) = J. If the ring S is pseudo-regular, then the set of S−maximal ideals of R is a complete lattice, isomorphic to the lattice of the ideals of S. In particular, the annihilator of S in R is the minimum of the S−maximal ideals of R. So the lattice structure of S−maximal ideals of R does not depend on the ring R.On the other hand, the ideals of S can be extended to ideals of R and the ideals of R can be restricted to ideals of S. These two processes are not adjoint to each other, but if we restrict to appropriated collections of ideals we can obtain adjunctions.